PEDOMAN PELAKSANAAN SUPERVISI PENDIDIKAN - Nuraini Nuraini (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Guidelines for the Implementation of Educational Supervision Permendiknas Number 12 of 2007 concerning Standards for School/Madrasah Supervisors states that every education unit supervisor is required to have six competencies, namely personal competence, managerial and academic supervision competence, educational evaluation competence, research and development competence, and social competence. Two main competencies are directly related to supervisory activities in educational units: managerial and academic supervision. Managerial supervision is intended to improve the quality of school management, while academic supervision is intended to improve the quality of teaching, which ultimately improves the quality of graduates. This supervision is very important because management is the engine of the organisation that drives all school programmes, including leadership, curriculum, student affairs, facilities and infrastructure, budgeting, community relations, etc. The guidelines for educational supervision in terms of policy are explained in Law No. 20 of 2003 on the National Education System, Law No. 14 of 2004 on Regional Government, Law No. 5 on the Civil Service, Government Regulation No. 19 of 2005, amended by No. 13 of 2015, amended by No. 19 of 2015 on National Education Standards, Government Regulation No. 74 of 2008 on Teachers and Lecturers, Government Regulation No. 17 of 2010 on Discipline for Supervisors, Presidential Regulation No. 14 of 2015 Ministry of Education and Culture.